Technological aspects of egg in the development of thermally coagulated ready to eat products - Prasad, Kamlesh; Lovina; Shekhar , Shubhra (Journal of Postharvest Technology, 2019)
India is the fourth largest producer of hens’ egg in the world with a production figure of 105 billion eggs per annum. Andhra Pradesh, Bihar, Karnataka, Maharashtra, Punjab, Tamilnadu, Telangana, and West Bengal, are the major states involved in the poultry production. In spite of large production, its per capita eggs consumption is 70 eggs per annum against a recommended set target of 180 eggs consumption per person per annum by National Egg Coordination Committee (NECC) and Indian Council of Medical Research (ICMR) . Considering the net protein utilization and protein efficiency ratio, egg is considered as the best source of protein apart from the other nutrient source. The thermal processing has a significant effect on the sensory, thermal, textural, nutritional, and microbial quality of processed egg-based products. An overview of technological aspects of egg in development of RTE product are presented which directly or indirectly affects the quality of final products.